A new control chart for monitoring the event frequency and magnitude. (1st January 2014) - Qu, L.; Wu, Z.; Khoo, M.B.C.; Shu, L.J.
This article presents a single statistical process control chart, the G chart, for monitoring a critical event through the simultaneously testing of the time interval T and magnitude X of the event. The G chart is not only able to make decisions based on both T and X, but is also capable to optimally allocate the detection power between that against T shifts and X shifts, and between that against small shifts and large shifts. Moreover, the G chart retains most of the advantages of the Shewhart type charts of easy design, implementation and understanding. The results of performance studies show that the G chart is much more effective than all other Shewhart charts in literature for detecting the out-of-control status of an event. The G chart can be applied to many areas, especially to non-manufacturing sectors such as supply chain management and healthcare industry.